"The Only Way Is Up": Overoptimism and the Demise of the American Five-and-Dime Store, 1914–1941. Issue 1 (10th May 2017) - Scott, Peter; Walker, James T.
Abstract : We examine a classic "wheel of retailing" episode: the abandonment of the five-and-dime pricing formula by American variety chains. The variety chains switched from a conventional product lifecycle, focusing on cost reduction through standardization, to a reverse path up the "service cost–unit value" continuum. We show that, rather than reflecting deteriorating managerial acumen, this shift was a response to the continued imperative for growth following retail format saturation. Firm-specific (rather than format-specific) competitive advantages were too weak for any chain to be confident it could win a within-format price war, making interformat competition through raising price points more attractive.